PtRu/C electrocatalysts prepared using electron beam irradiation - Silva,Dionísio Furtunato da (2007)
PtRu/C electrocatalysts (carbon-supported PtRu nanoparticles) were prepared submitting water/ethylene glycol mixtures containing Pt(IV) and Ru(III) ions and the carbon support to electron beam irradiation. The electrocatalysts were characterized by energy dispersive X ray analysis (EDX), X ray diffraction (XRD) and cyclic voltammetry and tested for methanol electro-oxidation aiming fuel cell application. The obtained PtRu/C electrocatalysts showed superior performance for methanol electro-oxidation at room temperature compared to commercial PtRu/C electrocatalyst.